(3OjhGf SdGeI Hf LfOds - (3SdGeI Hf LfOd Hf YHO YeQh GdJejej, CHh eGdcs
(3ChdgG (B:s
(3BhOi GdTHGH MejOkG Ph GdJYGLjH BhOi hPdc TC hZjQ eWdhH s
(3BNQgG (B:s
(3ZOGI JQcfG ef QHjYI YGeQ OeGA HCYdi GdhGOjjf JSjd s
(3GfXQ TYQ SdGeI Hf LfOd HGdLRA GdChd HQbe (B315 - (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B106 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B236s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjG UhajG (B(4904) s
Keywords: (3GdCOHs